Pharmacokinetics and dose escalation of the heat shock protein inhibitor 17-allyamino-17-demethoxygeldanamycin in combination with bortezomib in relapsed or refractory acute myeloid leukemia. Issue 9 (September 2013) - Walker, Alison R.; Klisovic, Rebecca; Johnston, Jeffrey S.; Jiang, Yao; Geyer, Susan; Kefauver, Cheryl; Binkley, Philip; Byrd, John C.; Grever, Michael R.; Garzon, Ramiro; Phelps, Mitch A.; Marcucci, Guido; et al.
Abstract: This phase I study was conducted to determine the maximum tolerated dose (MTD) and dose limiting toxicities (DLTs) of the heat shock protein 90 (HSP90) inhibitor 17-allyamino-17-demethoxygeldanamycin (17-AAG) in combination with bortezomib, and to provide pharmacokinetic data in relapsed or refractory acute myeloid leukemia (AML). Eleven patients were enrolled. The MTD was 17-AAG 150 mg/m 2 and bortezomib 0.7 mg/m 2 . Hepatic toxicity and cardiac toxicity were dose limiting. Co-administration on day 4 led to a decrease in clearance ( p = 0.005) and increase in AUC ( p = 0.032) of 17-amino-17-demethoxygeldanamycin (17-AG), not observed when 17-AAG was administered alone. Pharmacokinetic parameters of patients who developed toxicities and those who did not were not different. The combination of 17-AAG and bortezomib led to toxicity without measurable response in patients with relapsed or refractory AML. Pharmacokinetic data provide insight for studies of related agents in AML. Next-generation HSP90 inhibitors are appealing for further development in this area.